Evaluation of mitochondrial dysfunction due to oxidative stress in therapeutic, toxic and lethal concentrations of tramadol. Issue 6 (8th November 2021) - Mohammadnejad, Leila; Soltaninejad, Kambiz; Seyedabadi, Mohammad; Ghasem Pouri, Seyed Khosro; Shokrzadeh, Mohammad; Mohammadi, Hamidreza
Abstract: Tramadol (TR) is a centrally acting analgesic drug that is used to relieve pain. The therapeutic (0.1–0.8 mg/l), toxic (1–2 mg/l) and lethal (>2 mg/l) ranges were reported for TR. The present study was designed to evaluate which doses of TR can induce liver mitochondrial toxicity. Mitochondria were isolated from the five rats' liver and were incubated with therapeutic to lethal concentrations (1.7–600 μM) of TR. Biomarkers of oxidative stress including: reactive oxygen species (ROS), lipid peroxidation (LPO), protein carbonyl content, glutathione (GSH) content, mitochondrial function, mitochondrial membrane potential (MMP) and mitochondrial swelling were assessed. Our results showed that ROS and LPO at 100 μM and protein carbonylation at 600 μM concentrations of TR were significantly increased. GSH was decreased specifically at 600 μM concentration. Mitochondrial function, MMP and mitochondrial swelling decreased in isolated rat liver mitochondria after exposure to 100 and 300 μM, respectively. This study suggested that TR at therapeutic and toxic levels by single exposure could not induce mitochondrial toxicity. But, in lethal concentration (≥100 μM), TR induced oxidative damage and mitochondria dysfunction. This study suggested that ROS overproduction by increasing of TR concentration induced mitochondrial dysfunction and caused mitochondrial damage via Complex II and membrane permeability transition pores disorders, MMP collapse and mitochondria swelling. Graphical Abstract: